GEN Z SPEAKING ANXIETY IN EFL CONTEXTS: A COMPARATIVE STUDY OF INDONESIA AND VIETNAM - Safa Safariah; Nurul Hidayah; Faizatul Husna; Yahya Amin (Universitas Islam Sumatera Utara (UISU), 2026)
This study investigates how Generation Z students experience speaking anxiety, the strategies they employ to overcome it, and ways to build confidence in speaking English. Speaking anxiety is a common challenge among Generation Z learners in English as a Foreign Language (EFL) contexts, particularly where oral communication is emphasized. Using a qualitative approach, data were collected through semi-structured interviews with 10 female senior high school students from Indonesia and Vietnam selected through purposive sampling. All participants reported difficulties in oral performance due to speaking anxiety. The data were analyzed using thematic analysis to identify recurring patterns and themes related to students’ experiences and coping strategies. The findings revealed three major forms of speaking anxiety: communication anxiety, test anxiety, and fear of receiving poor grades. Students employed various coping strategies to manage their anxiety. Indonesian students tended to adopt informal approaches, such as practicing with peers and using digital media, whereas Vietnamese students relied more on structured learning resources, including language-learning applications. Cross-cultural differences were also identified. Indonesian students were more likely to experience anxiety stemming from social pressure, such as fear of embarrassment or being ridiculed, while Vietnamese students were more concerned with linguistic accuracy. By comparing Generation Z learners from Indonesia and Vietnam, this study provides a cross-cultural perspective on speaking anxiety and coping strategies in EFL settings. The findings offer practical implications for EFL teachers in developing culturally responsive approaches to enhance students’ speaking confidence and oral communication skills.